AN ANALYSIS OF QIRĀ’ĀT AND THE MEANING OF FASĀD IN QS. AL-BAQARAH VERSE 205 AND ITS RELEVANCE TO CONTEMPORARY ENVIRONMENTAL ISSUES - Ahmad Alfissalam; Muhammad Alfiyadi Khairun Ibrahim Akhsay; Najib Irsyadi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to analyze the variations of qirā’āt in QS. Al-Baqarah verse 205 and to examine the meaning of fasād contained within it, as well as its relevance to contemporary environmental issues. This research employs a qualitative method based on library research, using thematic interpretation (mawḍū‘ī) and linguistic approaches to Qur’anic exegesis. The data were collected from the Qur’an, classical and contemporary tafsīr works, as well as literature on qirā’āt and environmental studies. The findings reveal that there are variations in the readings of yuhlika (active) and yuhlaku (passive), along with differences in the grammatical position (i‘rāb) of al-ḥarth and al-nasl. These variations produce complementary meanings, where the active form emphasizes human beings as the agents of destruction, while the passive form highlights the widespread consequences. The concept of fasād in this verse encompasses not only moral and social corruption but also carries a strong ecological dimension. In the contemporary context, the concept of fasād is highly relevant to environmental issues such as deforestation, overexploitation of natural resources, and global ecological crises. The integrative analysis of qirā’āt and tafsīr demonstrates that the Qur’an provides a comprehensive conceptual framework for understanding destruction both as an action and as a consequence. Therefore, this verse can serve as a normative foundation for developing environmental awareness and ethics based on Qur’anic values.